Relasi Firmitas, Utilitas, dan Venustas pada Microlibrary Warak Kayu, Semarang - Febriana Andini Setya Ningrum, Gabriella; Danang H. Wibowo (Program Studi Arsitektur Institut Teknologi Nasional (ITN) Malang, 2024)
ABSTRACT The Warak Kayu Microlibrary by women Indonesian architects, Daliana Suryawinata and Florian Heinzelmann – SHAU Indonesia is dominated by wood materials that are displayed straightforwardly and clearly. Makes the expression of the building unusual. This work has received very wide coverage from many media, both domestically and abroad. In fact, Warak Kayu Microlibrary received the prestigious Architizer A+Awards 2020 organized by New York-based architectural media, United States, Architizer, in the Institutional-Libraries category and obtained, the Building of The Year Award 2021 in the Public and Landscape Architecture category from ArchDaily, and the Monsoon Architecture Award 2023 in the category Institution, Workplace and Commercial. However, not many have conducted academic studies on the work, especially related to firmity, utility, and venustas. This study uses a qualitative – descriptive approach with stages of studying aspects of the triad of Vitruvius theory by referring to the thoughts of Max Jacobson and Shelley Brock. Data collection is carried out by conducting field observations, conducting interviews with architects and users, and redrawing the object of study. The results of the study show that the relationship of firmitas, utilities, and venustas does not go hand in hand, especially related to firmity and utility. It is hoped that this research can be useful for architectural science, practitioners, and architecture students. Keywords : Warak Kayu Microlibrary, Firmitas, Utilitas, Venustas, Relationship.